2022
DOI: 10.1186/s41256-022-00249-z
|View full text |Cite
|
Sign up to set email alerts
|

Experience on the first national anti-TB drug resistance survey (DRS) in Timor-Leste

Abstract: Background A national drug resistance survey (DRS) was implemented for the first time in Timor-Leste (TL) in 2019. The primary objective of the survey was to assess the prevalence of drug resistance among new and previously treated pulmonary TB patients in the country. Methods This nation-wide cross-sectional survey was conducted in 2019 targeting all new and previously treated sputum smear-positive pulmonary TB patients. Sputum samples were submit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
2
1
1
Order By: Relevance
“…The recovered MTB study isolates were all phenotypically and genotypically susceptible to rifampicin, isoniazid, pyrazinamide, and ethambutol. These findings are consistent with data from the national anti-TB DRS, where low rates of resistance to first-line TB drug and MDR-TB were reported [ 5 , 18 ]. However, the small sample size and convenience sampling mean that resistance rates in Timor-Leste cannot be inferred from this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The recovered MTB study isolates were all phenotypically and genotypically susceptible to rifampicin, isoniazid, pyrazinamide, and ethambutol. These findings are consistent with data from the national anti-TB DRS, where low rates of resistance to first-line TB drug and MDR-TB were reported [ 5 , 18 ]. However, the small sample size and convenience sampling mean that resistance rates in Timor-Leste cannot be inferred from this study.…”
Section: Discussionsupporting
confidence: 92%
“…In 2012, the GeneXpert MTB/RIF (Cepheid, Sunnyvale, CA, USA) polymerase chain reaction (PCR) assay was introduced into the country. Since then, access to PCR testing has expanded, with the availability of 11 GeneXpert machines [ 5 ] in 8/13 municipalities, coordinated by the National Tuberculosis Control Program (NTP) and supported by the National TB Reference Laboratory (NTRL) at the National Health Laboratory (NHL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of sputum AFB-positive patients and MTBc detected by Xpert in our study was slightly lower than the rate reported in other drug-resistance surveys, ranging from 95.8% −97.7%(1417).…”
Section: Discussioncontrasting
confidence: 88%
“…Peran investigasi kontak serumah sangat kritikal dalam pengontrolan kasus TB secara global dan dibutuhkan untuk disesuaikan dengan latar belakang negara baik dengan beban TB yang rendah maupun tinggi (Yerramsetti et al, 2022). Program Penanggulangan TB mengubah strategi penemuan pasien TB tidak hanya "secara pasif dengan aktif promotif" tetapi juga melalui penemuan aktif secara intensif dan masif berbasis keluarga dan masyarakat (Lopes et al, 2022).…”
Section: Investigasi Kontak Serumah Dan Deteksi Diniunclassified